Recherches autour du dossier hagiographique de saint Arnoux, évêque de Gap († avant 1079): BHL 712 et édition de la Vie latine BHL 712b - Foulon, Jean-Hervé (Analecta Bollandiana, 2007)
The hitherto unpublished Vita BHL 712b found in codex Bibl. Angelica 1269 is the key document in the hagiographic file relating to St Arnold, monk of Vendôme and bishop of Gap († before 1079). This Vita prima Arnulphi, written in the 12th century in cathedral circles at Gap, is the source of the lessons in the office of the saint at the beginning of the 13th century. However, in order to meet the expectations of monastic circles in the Vendôme a Vita secunda (BHL 712) was compiled at the end of the 13th century. Its edition in the 18th century for a long time overshadowed the original Vita and it has become necessary to present a critical edition.